1997
DOI: 10.1111/j.1460-9568.1997.tb01367.x
|View full text |Cite
|
Sign up to set email alerts
|

Nociceptin/Orphanin FQ Microinjected into Hippocampus Impairs Spatial Learning in Rats

Abstract: The newly discovered peptide nociceptin/orphanin FQ has been found to increase reactivity to pain and to influence locomotor activity after intracerebroventricular administration. This study investigated the possible role of hippocampal nociceptin/orphanin FQ in spatial learning and in spontaneous locomotion. Male rats were trained in the Morris water task after microinjection of 10 nmol nociceptin/orphanin FQ or artificial cerebrospinal fluid (as control) into the CA3 region of the dorsal hippocampus. Nocicep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
107
0
1

Year Published

1999
1999
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 230 publications
(120 citation statements)
references
References 11 publications
11
107
0
1
Order By: Relevance
“…In summary, the results from the present study support and extend those of Sandin et al (1997) in that bilateral intrahippocampal (CA3 region) injection of nociceptin provoked marked impairments in spatial learning in the Morris water maze task, results which are consistent with the dense localization of OP 4 /nociceptin receptors in the hippocampal formation (Mollereau et al, 1994). Most interestingly, this study demonstrates that such learning impairments are truly mediated by OP 4 /nociceptin receptors, as pretreatment with the recently developed nociceptin receptor antagonist, [Nphe 1 ]-Nociceptin (1-13)-NH 2 , reversed nociceptin-induced de®cits in escape latency.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In summary, the results from the present study support and extend those of Sandin et al (1997) in that bilateral intrahippocampal (CA3 region) injection of nociceptin provoked marked impairments in spatial learning in the Morris water maze task, results which are consistent with the dense localization of OP 4 /nociceptin receptors in the hippocampal formation (Mollereau et al, 1994). Most interestingly, this study demonstrates that such learning impairments are truly mediated by OP 4 /nociceptin receptors, as pretreatment with the recently developed nociceptin receptor antagonist, [Nphe 1 ]-Nociceptin (1-13)-NH 2 , reversed nociceptin-induced de®cits in escape latency.…”
Section: Discussionsupporting
confidence: 90%
“…Such changes in locomotor activity were detected in the ®rst 5 min of testing, and support the use of a 3 min testing period in the present study. However, this subject remains controversial with both decreases (Reinscheid et al, 1995;Devine et al, 1996;Sandin et al, 1997) and increases (Florin et al, 1996) in locomotion being reported. A possible explanation is related to doses, with lower doses of nociceptin inducing increased locomotor activity while higher doses decreased exploratory locomotor behaviour.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations